A case study of Australia's emissions reduction policies - An electricity planner's perspective. (15th December 2020) - Byrom, Stephanie; Bongers, Geoffrey D.; Dargusch, Paul; Garnett, Andrew; Boston, Andy
Abstract: Australia offers an interesting case study of climate policy effectiveness as Australia has 'tried' a wide range of policies to mixed effect. Given that more than half of Australia's greenhouse gas emissions typically come from stationary energy generation, most climate policy in Australia has focussed on electricity sector reform, particularly the uptake of variable renewable energy and the decrease of thermal power generation. Electricity supply in Australia has undergone substantial change over recent years, substantially due to these policies, and needs to continue changing in the future to meet climate change mitigation targets and ensure stable, cost-effective electricity supply. This paper is therefore written from the perspective of an electricity planner and seeks to learn from the experiences of climate policies tried over recent decades. We start by reviewing the history of Australian energy policy and a description of how the Australian electricity network is structured to operate. We examine the theory and effects of different policies tried, which range from renewable energy targets, carbon pricing schemes, subsidies for renewable energy and research and development initiatives. We make three key observations from the case analysis: (1) that there has been substantial expense and effort effectively wasted through duplicate effects of different policy mechanisms by both federal and state governments; (2) as various mechanisms enable variable renewable energy generation to increase, the market becomes distorted, increasing total system costs and decreasing system robustness and resilience; and (3) the narrowed focus of climate policy mechanisms on certain variable renewables, such as solar photovoltaic and wind generation, omitted the opportunity for uptake of scale-able low carbon, firm generation options, like nuclear power and carbon capture and storage. Highlights: Australia has had a variable approach to emissions reduction to date. Policy duplication across federal and state levels leads to inefficiency. Market distortions can impact investment with negative system outcomes. Narrowing the policy path can discount options too early.